Analyzing the impact of the digital divide on e-commerce in Colombia (2019)
The aim of this study is to examine whether the digital divide has a moderating effect on the technological factors that affect the adoption of electronic commerce. This study propose an exploratory empirical model that integrates the basic variables of e-commerce adoption through the use of the technology adoption model (TAM), making an extension with the facilitating conditions and the digital divide as a moderating variable. A digital survey was randomly distributed in Colombia, reaching a final sample of 745 electronic buyers. The explanatory result validates that the perception of the digital divide negatively moderates the influence of the variables related to internet technology on the use of e-commerce. This is one of the first studies that analyzes the effect of the digital divide on the adoption of e-commerce. © 2019 International Business Information Management Association (IBIMA).